MAGEL2‐related disorders: A study and case series. Issue 6 (22nd August 2019) - Patak, Jameson; Gilfert, James; Byler, Melissa; Neerukonda, Vamsee; Thiffault, Isabelle; Cross, Laura; Amudhavalli, Shivarajan; Pacio‐Miguez, Marta; Palomares‐Bralo, Maria; Garcia‐Minaur, Sixto; Santos‐Simarro, Fernando; Powis, Zoe; et al.
Abstract: Pathogenic MAGEL2 variants result in the phenotypes of Chitayat‐Hall syndrome (CHS), Schaaf‐Yang syndrome (SYS) and Prader‐Willi syndrome (PWS). We present five patients with mutations in MAGEL2, including the first patient reported with a missense variant, adding to the limited literature. Further, we performed a systematic review of the CHS and SYS literature, assess the overlap between CHS, SYS and PWS, and analyze genotype‐phenotype correlations among them. We conclude that there is neither a clinical nor etiological difference between CHS and SYS, and propose that the two syndromes simply be referred to as MAGEL2 ‐related disorders. Abstract :